Pengaruh Fasilitas, Kualitas Pelayanan Petugas Dan Daya Tarik Obyek Wisata Terhadap Kepuasan Wisatawan Pada Wisata Pendakian - Heronimus Tri Panigoro; Sayekti, Rr. Nugraheni Suci; Askiyanto, Mohammad (Yayasan Lentera Avanya Nagari, 2025)
Tourist destinations that are popular with visitors lately, but behind their great potential, natural tourism also has various challenges that are faced, ranging from poor management, suboptimal service, and environmental damage. This kind of thing hinders the growth and development of tourism itself. The progress of tourism itself cannot be separated from the quality of service of the officers, the availability of facilities and the tourist attractions themselves, with the quality of services, facilities and good attractions in tourism, the better the level of tourism. So that the level of satisfaction of visitors with services, tourist facilities and tourist attractions can determine the level of tourism progress. The quantitative approach method is used in this researcher. The sample in the study was 100 people from the entire population who traveled. The results of the study showed that all the variables studied had a considerable influence on the satisfaction of tourists of Mount Bhutak, Batu City, East Java.